Effectiveness of biological agents to control Lepidiota stigma (Coleoptera: Scarabaeidae) larvae in endemic sugarcane plantation - Siswanto, Siswanto; Rohimatun, Rohimatun; Trisawa, Iwa Mara; Samsudin; Karmawati, Elna; Soetopo, Deciyanto; Ardana, I Ketut; Syakir, Muhammad; Mardiningsih, Tri Lestari; Indrayani, I Gusti Agung Ayu; Kardinan, Agus (Penerbit Universiti Kebangsaan Malaysia, 2025)
The information on the effectiveness of nematode and fungus entomopathogenic is essential for the appropriate management of white grubs Lepidiota stigma in endemic sugarcane plantations. Despite the significant benefits, there is still limited information on the management practices of white grubs control particularly in sugarcane plantations with sandy soil. Therefore, this study aimed to explore the effectiveness of Steinernema sp., Beauveria bassiana, and registered biological agents, as well as farmers’ methods in controlling white grubs. The Randomized Block Design was used to set up the experiment. The results showed that the three biological agents had a significantly lower population of white grubs compared to the control (untreated) at one month after treatment (MAT). At 3 and 4 MAT, the population of white grubs were also significantly lower compared to the untreated plots, suggesting that all treatments had suppressed the population in sandy soil. This was supported by the finding of the glasshouse trial which generally showed that the three biological agents were still effective in the soil media for a couple of weeks. Furthermore, this study showed that yields of sugarcane obtained from the application of the three biological agents produced economic benefits.